MEASUREMENT AKHLAK; SURVEI PADA SISWA SMA NEGERI DI PROVINSI JAWA TENGAH - Aji Sofanudin; Umi Muzayanah; A. M. Wibowo; Siti Muawanah; Mustolehuddin Mustolehuddin; Umi Masfiah (Al-Qalam, 2019)
This study aims to measure the akhlak index of state senior high school students in Central Java. This research is a quantitative survey of 1,202 state senior high school students in Central Java. The research findings show that akhlak is a physical activity as a manifestation of belief in carrying out the teachings of Islam. This student's akhlak limits itself to the activities of state senior high school students that are observed, not to things that are psychological. Based on the research, the akhlak index of state senior high school students in Central Java was 3.18. Of the five akhlakl dimensions (1) akhlak to Allah / Rasulullah is 2.82 (2) akhlak to oneself is 3.27 (3) akhlak to friends is 3.16 (4) akhlak to parents / teachers is 3, 40 (5) akhlak for the environment at 3.27. Of these five dimensions which are classified as low are akhlak towards Allah / Rasulullah.